Designing a new concept of narrow dynamic compression plate (narrow DCP) - Mohd Shahrulnizal, Ghozali (2007)
The objective of treating the fractured bone is to achieve painless functioning of the bone and undisturbed the healing process at the fracture site. Internal fixation by using bone plate, which is Narrow Dynamic Compression Plate (Narrow DCP) and screws is one of the standard methods to achieve these objectives. However, it is revealed that the stress protection under the plate led to osteoporosis and chances of re-fracture following its removal, which means the healing process, is disturbed. For the solution, the plate must be have undercuts on the undersurfaces of the plate between the screw holes that decrease amount of plate that contacts the surface of the bone. This will helps the adequate blood supply to the fracture site and the healing is undisturbed. So, the osteoprosis and the chances of re-fracture can be avoided. In this project, the strength of the new concept of Narrow DCP will be analyzed and the result will be compare to the present Narrow DCP. It is found that the new concept of the Narrow DCP is 12.7% less strength than the present bone plate because of decreasing the stress shielding in the plate.